ECO-FRIENDLY CONSUMERS IN THE FOURTH INDUSTRIAL REVOLUTION: ACADEMIC SOCIETY, GREEN CUSTOMERS, AND ECO LABELLING - Yanti Budiasih (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2018)
This analytical descriptive research aims to find out the relationship between the investigated variables. These variables had been previously tested hence this study made several modifications. The data consisted of primary data and involved 150 students of Ahmad Dahlan Economics School as the respondents. The research variables were divided into exogenous variables (i.e., eco labeling, eco knowledge, green product, green packaging and green advertising) and endogenous variables (i.e., purchase intention and green customer). The data analysis technique was the Partial Least Square (PLS) by using SmartPls software. Based on the results of hypothesis testing, it can be concluded that: eco-knowledge has a significant negative influence on purchase intention; eco-knowledge has a significant negative influence on green customers; eco-labeling has a significant positive influence on purchase intention; eco-labeling has a significant negative influence on green customer; green product has a significant positive influence on purchase intention; green product has a significant positive influence on green customer; green packaging has an insignificant influence on purchase intention; green packaging has an insignificant influence on green customer; green advertising has a significant negative influence on purchase intention; green advertising has a significant positive influence on green customer; and purchase intention has a significant positive influence on green customer.